Penguatan Perspektif Sociopreneurship bagi Orang Muda melalui Minitalkshow - Pratama, Aryan Agus; Gultom, Fahrian Arsyam; Zulfahmi; Andhi Pebisatria; Fikah (Jurnal Ilmiah Pengabdian dan Inovasi, 2025)
Global technological changes have shifted the business paradigm, requiring business activities to not only be profit-oriented, but also capable of creating social value. This phenomenon requires the younger generation to not only be competent business people, but also play an active role in creating a positive social impact. This activity aims to strengthen the perspective of sociopreneurship and increase critical awareness of the importance of integrating economic and social aspects among the younger generation. The activity was carried out through a mini-talkshow, which reached audiences both offline and online. The results of the activity showed that sociopreneurship learning can be effectively internalized through an action-reflective approach, integrating managerial, entrepreneurial, and social responsibility aspects. These findings confirm that higher education has a strategic role as a space for developing the capacity of the younger generation to become competent, ethical, and socially sustainable business actors. This activity also instilled a new spirit and encouraged the younger generation to play an active role in creating positive social change in their surroundings, while strengthening their social value-based entrepreneurial competencies.